Studi Identifikasi Lokasi Pendaratan Ikan Dalam Rangka Pengembangan Perikanan Laut di Pantai Selatan Daerah Istimewa Yogyakarta. - Perpustakaan UGM, i-lib ([Yogyakarta] : Fac. of Geography Gadjah Mada Univ., 2001)
ABSTRACT Along the coastline of Yogyakarta Province (DIY), which is about 110 km long, there are 19 fish landings. Fishermen use canoes to catch fish in coastal area. The production of marine fish is only 575 ton/year with a value of Rp 3 billion (Pustek Kelautan, 2000). This value is only 0,04 % of tke DIY GDP (gross regional domestic product) (Anonim, 1998). The potency of marine fish resource in coastal water, offshore of south coast of Java, and offshore of Indonesian Ocean respectively are 3,400 tons, 319,200 tons, and 905,350 tons (Divas Perikanan, 2000). One of the main constrains of the marine fish production in DIY is that there are no port to land big ships (more than 30 GT) which can operate on the offshore. The study is done to identify the 19 fish landings as site for a future development of the fisheries sector. The evaluation is based on the physical condition of fish landing sites such as access road, hinterland, area avaibility, oceanographical condition and supporting fasilities such as electricity, water supply, and communication. The study leads to recommend a future development of each fish landing. Serang rivermouth at Glagah coast is proposed as the fishing port. This location is near to the national road (2.5 km), with good supporting hinterland (near big town : Wates 10km, Yogyakarta 40 km, Puworejo 25 km, Kebumen 45 km, and Magelang 60 km), it has wide coastal area for port development, and many supporting facilities. But, this location is subject to heavy swell from the Indonesian Ocean. Therefore the port has to be protected by break water, which is a very high cost structure.